GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 76188 species occurrences available in GBIF matching the query: Country: Lao People's Democratic Republic. The dataset includes 76188 records from 230 constituent datasets: 3 records from Selenops muehlmannorum spec. nov. from Southern Laos (Araneae: Selenopidae). 51 records from Ehime University Coleoptera Collection. 22 records from Collection Coleoptera SMF. 1 records from Field Museum of Natural History (Zoology) Fish Collection. 194 records from Natural History Museum, University of Tartu. 7 records from Systematics of the family Ariidae (Ostariophysi, Siluriformes), with a redefinition of the genera.. 4 records from Freshwater Fish Specimens of Lake Biwa Museum. 4 records from UCBG TAPIR Provider. 1 records from Ompok platyrhynchus, a new silurid catfish (Teleostei: Siluridae) from Borneo.. 9 records from Collection Lepidoptera SMF. 2 records from Hemiptera (Homoptera) collection of National Museum of Nature and Science. 9 records from Hemiptera collection (EH) of the Muséum national d'Histoire naturelle (MNHN - Paris). 6 records from Chinese Institute of Biology - Chinese Academy of Sciences. 1 records from UCD BOTANICAL CONSERVATORY. 25 records from Herbarium specimens of Université de Montpellier 2, Institut de Botanique (MPU)). 146 records from EURISCO, The European Genetic Resources Search Catalogue. 28 records from Academy of Natural Sciences OBIS Mollusc Database. 295 records from Bernice P. Bishop Museum. 13 records from Collection Paleobotanique de l'Universite Paris 6. 1 records from Naturalis Biodiversity Center (NL) - Amphibia and Reptilia. 9 records from Entomology at ZMUC, Natural History Musem of Denmark. 20 records from Naturalis Biodiversity Center (NL) - Botany Utrecht. 1 records from Heteroptera. 38 records from The New York Botanical Garden Herbarium (NY) - Vascular Plant Collection. 29 records from UF FLMNH Ichthyology. 104 records from Harvard University Herbaria. 3 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Coleoptera_Types_Orient. 45 records from Missouri Botanical Garden. 3144 records from Royal Botanic Garden Edinburgh Herbarium (E). 36 records from UMMZ Birds Collection. 392 records from Collection Mammalia SMF. 5 records from Collection Thysanoptera SMF. 7 records from Bird Specimens in the Museum of Nature and Human Activities, Hyogo, Japan. 6 records from Invertebrates Collection of the Swedish Museum of Natural History. 1 records from Fish Collection of Kanagawa Prefectural Museum of Natural History. 1 records from Kyushu University Museum Coleoptera Collection. 1 records from NPL collections. 349 records from AMNH Mammal Collections. 1 records from Carnet en Ligne. 194 records from Mammals collection (ZM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1 records from Natural History Museum Rotterdam (NL) - Mollusca collection. 571 records from Botany (UPS). 1 records from Field Museum of Natural History (Botany) Seed Plant Collection. 2 records from CAS Herpetology (HERP). 5 records from Entomological Collections (NHRS), Swedish Museum of Natural History (NRM). 12 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Herpetology. 1 records from CZE National PGR Inventory. 1 records from Database of Native Plants in Taiwan. 2 records from CAS Mammalogy (MAM). 3 records from Kryptopterus geminus, a new species of silurid catfish (Teleostei: Siluridae) from mainland Southeast Asia.. 2 records from Vertebrate Zoology Division - Mammalogy, Yale Peabody Museum. 141 records from Estacion Biologica Donana - CSIC, Mammal Collection. 3 records from The identity of Pseudecheneis sulcata (M'Clelland, 1842), with descriptions of two new species of rheophilic catfish (Teleostei: Sisoridae) from Nepal and China.. 6 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 28 records from The Herpetology Collection at the Staatliches Museum für Naturkunde Stuttgart. 6 records from Geneva Herbarium – General Collection (G). 261 records from South Australian Museum Australia provider for OZCAM. 38 records from Estonian Museum of Natural History. 13 records from SINGER Coordinator. 439 records from Field Museum of Natural History (Zoology) Insect, Arachnid and Myriapod Collection. 173 records from Zoologische Staatssammlung Muenchen - International Barcode of Life (iBOL) - Barcode of Life Project Specimen Data. 3082 records from Field Museum of Natural History (Zoology) Bird Collection. 7 records from Therevid PEET Project. 9 records from Genera of the Asian Catfish Families Sisoridae and Erethistidae (Teleostei: Siluriformes).. 3 records from Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 4 records from Itami City Museum of Insects. 195 records from UCM Fish Collection (Arctos). 60 records from Collection Mollusca SMF. 1 records from Ornithology Collection Passeriformes - Royal Ontario Museum. 5 records from herpetology. 38 records from Myriapoda - SMF. 66 records from Collection Crustacea SMF. 132 records from Entomological Specimens of Museum of Nature and Human Activities, Hyogo Pref., Japan. 139 records from Naturalis Biodiversity Center (NL) - Mammalia. 1237 records from Reptiles and Amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 5 records from Pseudecheneis maurus, a new species of glyptosternine catfish (Teleostei: Sisoridae) from Central Vietnam.. 36 records from Entomology Division, Yale Peabody Museum. 2 records from Museu de Ciències Naturals de Barcelona: MCNB-Art. 62 records from Field Museum of Natural History (Zoology) Amphibian and Reptile Collection. 4 records from Centre for Genetic Resources, the Netherlands, PGR passport data. 2 records from Naturalis Biodiversity Center (NL) - Crustacea. 10 records from Naturalis Biodiversity Center (NL) - Chelicerata and Myriapoda. 1 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Pisces_Types. 24 records from Snow Entomological Museum Collection. 25 records from Lund Museum of Zoology - Insect collections (MZLU). 305 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 84 records from Naturalis Biodiversity Center (NL) - Mollusca. 83 records from ORN. 4 records from New country records of reptiles from Laos. 4433 records from Vascular plants collection (P) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1 records from Naturalis Biodiversity Center (NL) - Lepidoptera. 21 records from Collection Pisces SMF. 4 records from Two new glyptosternine catfishes (Teleostei: Sisoridae) from Vietnam and China.. 34 records from Biologiezentrum Linz. 550 records from Birds collection (ZO) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1 records from UMMZ Mammal Collection. 1 records from New Zealand Fungal and Plant Disease Collection (PDD). 502 records from SMNK Mantid Collection. 42 records from Australia's Virtual Herbarium. 1 records from Orthopteroidea. 28 records from ECatSym: Electronic World Catalog of Symphyta. 1 records from Arachnida e Myriapoda Museu Nacional (MNRJ ARAC). 5768 records from Natural History Museum (London) Collection Specimens. 4 records from Mammalogy Collection - Royal Ontario Museum. 11 records from Crustacea ZMK. 2 records from Collection Ornithologie - SNSD. 1 records from Field Museum of Natural History (Botany) Lichen Collection. 2 records from Collection Herpetology SMF. 4 records from Northern Territory Museum and Art Gallery provider for OZCAM. 31 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Types. 422 records from CAS Ichthyology (ICH). 138 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mammalia. 2328 records from Museum of Comparative Zoology, Harvard University. 3 records from Six new species of the spider family Ochyroceratidae Fage 1912 (Arachnida: Araneae) from Southeast Asia. 133 records from Royal Botanic Garden Edinburgh Living Plant Collections (E). 7 records from Texas A&M University Insect Collection. 2 records from Marie-Victorin Herbarium (MT) - Plantes vasculaires. 18 records from Collection Herpetologie - SNSD. 158 records from NRM-Fishes. 460 records from Field Museum of Natural History (Zoology) Mammal Collection. 32 records from Revision of the genus Sinopoda Jäger, 1999 in Laos with discovery of the first eyeless huntsman spider species (Sparassidae: Heteropodinae). 1 records from Naturalis National Natural History Museum (NL) – Aves_ Passeriformes. 5 records from Edaphobase. 475 records from Fishbase. 1 records from Naturalis National Natural History Museum (NL) – Crustacea_Decapoda. 43 records from Fish Collection of Natural History Museum and Institute, Chiba. 6475 records from Naturalis Biodiversity Center (NL) - Botany Leiden. 7 records from CM Birds Collection. 6 records from Mosquito Occurrence Dataset. 2 records from North Carolina State Museum of Natural Sciences Fishes Collection. 1 records from Field Museum of Natural History (Botany) Bryophyte Collection. 6582 records from Naturalis Biodiversity Center (NL) - Botany. 35 records from Herbarium of The New York Botanical Garden. 1 records from Parasitic Platyhelminthes Collections. 2044 records from NCSM Herpetology Collection. 34 records from naturgucker. 100 records from AMNH Herpetology Collections. 4 records from Crustacea Collection of Natural History Museum and Institute, Chiba. 11 records from The AAU Herbarium Database. 20 records from Collection Aves (bird skeletons) SMF. 1 records from Kryptopterus platypogon, a new silurid catfish (Teleostei: Siluridae) from Borneo.. 42 records from Paleobiology Database. 10 records from Mammal collection of National Museum of Nature and Science. 4 records from Revalidation and redescription of Pterocryptis anomala (Herre, 1933), a catfish (Teleostei: Siluridae) from southern China.. 2818 records from EOD - eBird Observation Dataset. 3 records from MfN Fish Collection, Zoology. 25 records from Harold W. Manter Laboratory of Parasitology Collection. 3 records from An updated checklist of aquatic plants of Myanmar and Thailand. 48 records from Mammals housed at MHNG, Geneva. 4 records from C.A. Triplehorn Insect Collection (OSUC), Ohio State University. 18 records from CABI Bioscience Fungus Collection. 1 records from National Museum of Natural Science. 11 records from Insecta ZMK. 4 records from Fossil collection (F) of the Muséum national d'Histoire naturelle (MNHN - Paris). 19 records from Coleoptera collection (EC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 2 records from University of California Museum of Paleontology. 3 records from Pseudecheneis suppaetula, a new species of glyptosternine catfish (Teleostei: Sisoridae) from India.. 5 records from CUMV Bird Collection (Arctos). 30 records from UMMZ Herpetology Collection. 27 records from Fish collection of National Museum of Nature and Science. 1 records from Herpetology Collection - Royal Ontario Museum. 1 records from Ohio State Acarology Laboratory (OSAL), Ohio State University. 13 records from Clubionidae from Laos and Thailand (Arachnida: Araneae). 9 records from Scorpiones collection (RS) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1381 records from Collection Arachnology SMF. 67 records from Coleoptera collection of National Museum of Nature and Science. 36 records from Lepidoptera specimen database of Japan. 2 records from Natural History Museum, Vienna - Herbarium W. 3 records from Akysis pulvinatus, a new species of catfish (Siluriformes: Akysidae) from southern Thailand.. 15 records from Herbarium Berolinense. 265 records from RBINS collections. 3 records from Museo Nacional de Ciencias Naturales, Colección de Malacología. 28 records from invertebratezoology. 4 records from Global subterranean fishes. 2 records from SysTax - Herbaria. 36 records from Molluscs collection (IM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1 records from The Collection of Fungi of the Real Jardín Botánico of Madrid (MA-Fungi). 10 records from Platynotina (Coleoptera: Tenebrionidae) collections on the World. 30 records from NCSM Invertebrates Collection. 5 records from AntWeb. 11 records from SysTax - Zoological Collections. 2 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 758 records from Geographically tagged INSDC sequences. 2 records from Fungi (S). 26 records from Australian National Herbarium (CANB). 276 records from Fishes collection (IC) of the Muséum national d'Histoire naturelle (MNHN - Paris). 6 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Aves. 1 records from Lichen Collection of National Museum of Nature and Science. 27 records from Hemiptera (Heteroptera) collection of National Museum of Nature and Science. 3 records from NSW herbarium collection. 6 records from University of Vienna, Institute for Botany - Herbarium WU. 22 records from Naturalis Biodiversity Center (NL) - Botany Wageningen. 13 records from United States National Plant Germplasm System Collection. 12 records from PRECIS. 642 records from Phanerogamic Botanical Collections (S). 2 records from Image Database of Fishes in the Kanagawa Prefectural Museum of Natural History. 1 records from A new species of the Asian schilbid catfish genus Clupisoma from Myanmar, with a redescription of Clupisoma prateri Hora (Osteichthyes: Siluriformes: Schilbidae).. 3 records from Two new species of Pseudecheneis, rheophilic catfishes (Teleostei: Sisoridae) from Nepal.. 14951 records from The System-wide Information Network for Genetic Resources (SINGER). 3764 records from Vertebrate Zoology Division - Ornithology, Yale Peabody Museum. 4 records from Hymenoptera specimen database of Kyushu University. 7 records from IndOBIS, Indian Ocean Node of OBIS. 1 records from Nematodes collection (IN) of the Muséum national d'Histoire naturelle (MNHN - Paris). 2 records from A geographic distribution database of the cassava whitefly complex (Hemiptera, Aleyrodidae) and their associated parasitoids and hyperparasitoids (Hymenoptera). 3 records from New species of the spider genus Olios Walckenaer, 1837 (Araneae: Sparassidae: Sparassinae) from Laos. 8 records from Mosses (S). 4 records from The Arthropoda Varia Collection at the Zoologische Staatssammlung München. 4 records from Mammal specimens. 2 records from NCSM Fishes Collection. 3 records from Akysis longifilis, a new species of catfish (Teleostei: Akysidae) from Myanmar.. 1 records from NRM-Herpetology. 3 records from DMNH Birds. 1716 records from MAL. 10 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 888 records from Nationaal Herbarium Nederland. 2 records from Flora of Japan Specimen Database. 40 records from LACM Vertebrate Collection. 2 records from Australian Museum provider for OZCAM. 33 records from Cryptogamy collection (PC) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 3012 records from Australian National Wildlife Collection provider for OZCAM. 14 records from Osaka Prefectural Minoh Park Insects Museum. 1 records from Herbarium specimens of Société des Sciences Naturelles et Mathématiques de Cherbourg (CHE). 6 records from Naturalis National Natural History Museum (NL) – Insecta_Lepidoptera_SE Asia and other regions. 195 records from AMNH Bird Collection. 2 records from Akrokolioplax, a new genus of Southeast Asian labeonine fishes (Teleostei: Cyprinidae).. 1136 records from NMNH occurrence DwC-A. 5 records from Araneae collection (AR) of the Muséum national d'Histoire naturelle (MNHN - Paris). 1 records from The identity of Pseudomystus moeschii (Boulenger, 1890), with the description of two new species of bagrid catfishes from Southeast Asia (Teleostei: Bagridae).. 30 records from Entomological collection of the National Museum. 3 records from Herbarium specimens of Herbiers Universitaires de Clermont-Ferrand (CLF).
Keywords: GBIF; biodiversity; species occurrences